2022
DOI: 10.1155/2022/7140066
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Preventive Action of Rivaroxaban against Lower Extremity Deep Venous Thrombosis in Patients after Laparoscopic Radical Gastrectomy

Abstract: Background. Gastric carcinoma (GC) is a common lethal cancer in the world. Patients are prone to develop lower extremity deep venous thrombosis (LEDVT) after laparoscopic radical gastrectomy (LRG), which threatens their life and health. Purpose. This research is to clarify the preventive action of rivaroxaban (Riv) against LEDVT in patients undergoing LRG. Methods. A retrospective study was conducted on 70 patients with GC admitted for LRG between January 2019 and January 2022, including 40 patients (observati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
0
0
Order By: Relevance
“…Notably, GC surgery is linked to a heightened risk of postoperative VTE, including DVT and PE 14 , 15 . Compared with air wave pressure therapy instrument, rivaroxaban has better preventive effect on lower extremity DVT after GC operations 16 . A systematic review and meta-analysis involving 111,936 patients indicated that the 1-month incidence of VTE post GC surgery was 1.8%, and specifically for DVT, it was 1.2% 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Notably, GC surgery is linked to a heightened risk of postoperative VTE, including DVT and PE 14 , 15 . Compared with air wave pressure therapy instrument, rivaroxaban has better preventive effect on lower extremity DVT after GC operations 16 . A systematic review and meta-analysis involving 111,936 patients indicated that the 1-month incidence of VTE post GC surgery was 1.8%, and specifically for DVT, it was 1.2% 11 .…”
Section: Discussionmentioning
confidence: 99%